Enhancing English Vocabulary Reading Skills Through Audiovisual Phonics Instruction: A Classroom Action Research on Students with Specific Learning Difficulties - Nurhidaya, Nurhidaya; Pujaningsih, Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
This study aims to improve English vocabulary reading skills among junior high school students with specific learning difficulties through the implementation of an audiovisual phonics-based instructional method. Conducted as a Classroom Action Research (CAR) using the Kemmis and McTaggart model, the research involved four Grade VII students at SMP Negeri 1 Kaliorang during the 2024/2025 academic year. The intervention was delivered in two cycles, each comprising planning, action, observation, and reflection phases. Instructional strategies were designed to enhance phoneme recognition, sound-symbol correspondence, and contextual vocabulary acquisition through multimodal media, including slow-paced videos and interactive visual aids. Data were collected via pre- and post-tests, observation sheets, and student participation checklists. The results showed consistent improvement in students’ vocabulary reading performance, with all participants exceeding the 80% mastery threshold by the end of Cycle II. Teacher implementation scores rose from 77% to 97%, while student engagement increased significantly across sessions. The findings suggest that audiovisual phonics instruction, when combined with structured scaffolding and adapted media, can effectively support vocabulary development among students with reading difficulties. However, further research is recommended to validate the method’s effectiveness in broader and more diverse educational contexts.